T-type Ca(2+) Channels Promote Oxygenation-induced Closure of the Rat Ductus Arteriosus Not Only by Vasoconstriction but Also by Neointima Formation - Akaike, Toru (American Society for Biochemistry and Molecular Biology, 2009)
The ductus arteriosus (DA), an essential vascular shunt for fetal circulation, begins to close immediately after birth. Although Ca(2+) influx through several membrane Ca(2+) channels is known to regulate vasoconstriction of the DA, the role of the T-type voltage-dependent Ca(2+) channel (VDCC) in DA closure remains unclear. Here we found that the expression of α1G, a T-type isoform that is known to exhibit a tissue-restricted expression pattern in the rat neonatal DA, was significantly up-regulated in oxygenated rat DA tissues and smooth muscle cells (SMCs). Immunohistological analysis revealed that α1G was localized predominantly in the central core of neonatal DA at birth. DA SMC migration was significantly increased by α1G overexpression. Moreover, it was decreased by adding α1G-specific small interfering RNAs or using R(−)-efonidipine, a highly selective T-type VDCC blocker. Furthermore, an oxygenation-mediated increase in an intracellular Ca(2+) concentration of DA SMCs was significantly decreased by adding α1G-specific siRNAs or using R(−)-efonidipine. Although a prostaglandin E receptor EP4 agonist potently promoted intimal thickening of the DA explants, R(−)-efonidipine (10(−6) m) significantly inhibited EP4-promoted intimal thickening by 40% using DA tissues at preterm in organ culture. Moreover, R(−)-efonidipine (10(−6) m) significantly attenuated oxygenation-induced vasoconstriction by ∼27% using a vascular ring of fetal DA at term. Finally, R(−)-efonidipine significantly delayed the closure of in vivo DA in neonatal rats. These results indicate that T-type VDCC, especially α1G, which is predominantly expressed in neonatal DA, plays a unique role in DA closure, implying that T-type VDCC is an alternative therapeutic target to regulate the patency of DA.